Yoldiella valorousae Killeen & J. A. Turner 2009 ... - Gofas, Serge; Luque, Ángel A.; Oliver, Joan Daniel; Templado, José; Serrano, Alberto (Zenodo, 2021)
Yoldiella valorousae Killeen & J.A. Turner, 2009 Fig. 32I‒J Material examined GALICIA BANK • 2 spm, 2 sh; 43°00.12′ N, 11°57.67′ W; 1706 m; 29 Jul. 2011; BANGAL 0711 V2; MNCN • 2 sh, 1 v; 42°56.77′ N, 11°58.53′ W; 1631 m; 2 Aug. 2011; BANGAL 0711 V5; MNCN • 1 v; 42°41.87′ N, 11°26.71′ W; 1720 m; 8 Aug. 2011; BANGAL 0711 V10; MNCN • 1 v; 42°32.16′ N, 12°03.79′ W; 1585 m; 5 Aug. 2011; BANGAL 0711 DR12; MNCN. Remarks There is a complicated nomenclatural and taxonomic history for the small Yoldiella species originally described by Jeffreys (1876) as Leda lata, from abyssal depths of the North Atlantic. The name is a secondary homonym of Nucula lata Hinds, 1843, for which reason it was renamed Leda jeffreysi Hidalgo, 1877. Allen et al. (1995) considered that Jeffreys’ type material comprised two different species; they used the preoccupied name Yoldiella lata for one of them and the replacement name Yoldiella jeffreysi for the other one, disregarding the nomenclatural rule (ICZN Art. 72.7) which makes them ... : Published as part of Gofas, Serge, Luque, Ángel A., Oliver, Joan Daniel, Templado, José & Serrano, Alberto, 2021, The Mollusca of Galicia Bank (NE Atlantic Ocean), pp. 1-114 in European Journal of Taxonomy 785 (1) on page 76, DOI: 10.5852/ejt.2021.785.1605, http://zenodo.org/record/5798418 ...